Magnetic Perovskites Synthesis, Structure and Physical Properties - Kundu, Asish K.; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2016)
Magnetic perovskite with multi functional properties (magneto-resistive, magneto-dielectric, multiferroics, spintronics, etc.) have attracted increasing attention due to their possible applications towards storage materials and intriguing fundamental Physics. Despite the numerous investigations on multi functional materials in the past few years, a very few magnetic perovskites have been known to realize as ferromagnetic-insulators. In perovskites centred transition metal oxides strong interplay between lattice, charge, spin and/or orbital degrees of freedom provide a fantastic playground to tune their physical properties. The main purpose of this book is to introduce the phenomenon and physics of complex magnetism (phase separation, spin glass, frustrations, etc.) in perovskite manganites and cobaltites via an experimental approach. The book is organized into four chapters; Chap. 1 gives a brief introduction of various interesting phenomena in magnetic perovskites. Chapter 2 describes the results of the investigations on electronic phase separation and glassy ferromagnetism of the hole-doped perovskite manganites and cobaltites. Ordered and disordered effects and related aspects in hole-doped perovskite cobaltites are described in Chap. 3. Finally, in Chap. 4 the bismuth based magnetic perovskite is discussed.
Introduction to Magnetic Perovskites -- Electronic Phase Separation & Glassy Behavior in Magnetic Perovskites -- Ordered-Disordered Magnetic Cobalt Perovskite -- Bismuth Centred Perovskite Multiferroics.
Keywords: Optical materials; Ceramic materials; Condensed matter; Optical Materials; Ceramics; Condensed Matter Physics